Characterization and pathogenicity of Aeromonas hydrophila isolated from freshwater fishes - Hamdan, Ruhil Hayati (2017)
Aeromonas hydrophila is ubiquitous in aquatic habitat but frequently causes ulcerative disease known as red sore disease, red rot disease and motile Aeromonas septicemia (MAS) disease in cultured and feral fish. The disease is common worldwide and resulted in million dollar economic losses in the freshwater fish farming industry. Thus, this study was carried out to identify morphological, biochemical and physiological characteristics of A. hydrophila isolated from clinically infected freshwater fish in the state of Selangor, Malaysia. All sampled fish showed non-specific clinical signs such as skin hemorrhages, sunken eyes and fin rot. Forty isolates of A. hydrophila were isolated from 150 wild and farmed fishes by direct streakings from skin, kidney, spleen and liver and overlaid onto trypticase soy agar. Species of fish sampled were Black tilapia, Oreochromis mossambicus(n=30); Red hybrid tilapia,Oreochromis sp.(n=30); Jade perch,Scortum barcoo(n=25); Javanese carp,Puntius gonionotus(n=10); River carpLeptobarbus hoevenii(n=10), River catfish,Pangasius pangasius(n=10); Climbing perch,Anabas testudineus(n=10); African catfish,Clarias gariepinus(n=20) and Louhan,Cichlasomasp. (n=5). All isolates were identified using commercial kit, API 20E in combination with Gram staining, oxidase, catalase, vibriostatic agent, NaCl tolerance, temperature tolerence and hemolytic activity. Morphologically, all isolates were short rods, Gram negative and motile. The biochemical tests showed positive results for oxidase, catalase, ONPG, ADH, LDC, citrate utilization, indole production, gelatinase and Voges Proskauer. Besides, negative results were obtained from ODC, H2S, urease, TDA. Acid was produced from glucose, mannitol and arabinose. No acid production from inositol, sorbitol, rhamnose, saccharose, melibiose and amygdalin. All isolates grew in 0% and 3% NaCl. The bacterial isolates also grew at 22ºC and 37ºC. All isolates showed β-hemolysis on horse blood agar. Furthermore, A. hydrophila isolates were further confirmed using 16S rDNA sequencing.In the present study, the presence of virulence genes in 40 isolates of A. hydrophila obtained from freshwater fishes was carried out using polymerase chain reaction (PCR). The ten virulence genes were cytotonic heat-labile (alt), cytotonic heat-stable enterotoxins (ast), cytotoxic heat-labile enterotoxin (act), hemolysin (hly), aerolysin (aer), flagella A and flagella B (fla), lipase (lip), elastase (ela), serine protease (ser), and DNases (exu). All isolates contain lip,exuand sergenes. But, none of them contain ela,altand lafgenes. Almost all the isolates have hly(95%) and aer(75%) genes. 30% of the A. hydrophilaisolates showed the presence of astand actgenes. Twelve out of 40 isolates have the highest genes content (lip+, exu+, ast+, act+, hly+, aer+, ser+) while, two isolates have the lowest genes combination (lip+, exu+, ser+).Aeromonas hydrophilaisolated from Louhan fish (AHFH40) which contained high combination of virulence genes (lip+, exu+, ast+, act+, hly+, aer+, ser+) was chosen for experimental infection in Oreochromissp. Healthy juveniles of Oreochromis sp.(average size of 4 inches) were injected intraperitoneally with 0.1 ml of A. hydrophilasuspension containing 103, 104, 105, 106,107and 108cfu/ml. Susceptibility to experimental infection was expressed as LD50calculated by the method of Reed and Muench (1938). Haematological and biochemistry parameters were obtained from the control and experimentally infected fish at day 1, 3, 5 and 7. Significant reductions were observed in the hemoglobin content at 7 days post inoculation with A. hydrophila.The mean values of RBC, PCV and Hb showed fluctuation, but they were significantly lower (P<0.05) than those of the controls at 3, 5 and 7 dpi. Compared to the control group, the infected fish showed decreased in MCHC and MCH mean values at 5 and 7dpi. The WBC mean values of infected fish showed higher significant changes at 5 and 7dpi, respectively. Mean biochemical indices of TP, ALT and AST levels also fluctuated, and there were significant differences (P<0.05) between the infected and control groups. The glucose levels in infected fish were initially increased significantly (P<0.05) from the control mean values. Fishes showed clinical signs of MAS were sacrificed for histopathological assessment. Tissues from kidney, liver and spleen were fixed in 10% buffered formalin, processed and embedded into paraffin wax blocks. The sections were cut at 3-4 μm thick and stained with haematoxylin and eosin. Current results showed the LD50 ofA. hydrophilato Oreochromissp. was calculated ranging between 104and 105cfu/ml. Histopathological changes which included mononuclear cell infiltration, necrosis and hemorrhages in the kidney, liver, spleen and hepatopancreas were postulated due to the cytotoxin produced by the bacteria. Additionally, antibiotic sensitivity test, plasmid profiling and integron detection of Aeromonas hydrophila were also carried out. The isolates were tested for sensitivity to 10 antibiotics namely, penicillin G, cephalexin, florfenicol, streptomycin, kanamycin, erythromycin, ampicilin, gentamicin, oxytetracycline and tetracycline. Then, Multiple Antibiotic Resistance (MAR) index was calculated to determine the usage of antibiotics by fish farmers. Besides, polymerase chain reaction was carried out to detect integrase genes Int1,Int2 and Int3, gene cassette, integron-associated aadA,sul1 and qac1 genes, streptomycin resistance genes strA-strB, β-lactamase resistance genes blaTEM and blaSHV, and tetracycline resistance genes tetA-E and tetM. In the present study, A. hydrophila was shown to be sensitive to erythromycin, florfenicol, kanamycin and oxytetracycline, while they were resistance to cephalotin, gentamicin and penicillin -G. Furthermore, Multiple Antibiotic Resistance (MAR) index for the bacterial isolates was ranging from 0.4 to 0.5. The current MAR results indicated that the A. hydrophila in these farmed fish might have been indiscriminately and continuously exposed to those antibiotics during the fish culturing stages. Twelve out of 40 isolates contained plasmid DNA bands with sizes ranging from 6 to 23 kb. There was a little variation in the plasmid sizes observed. In addition, no particular plasmid profiles were predictive of a particular pattern of antibiotic resistance. The intl1 gene was detected in 50% (20/40) of A. hydrophila strains but no isolates contain intl2 and intl3. No gene cassette was detected from all the A. hydrophila isolates. The aadA was found in 5/40 (12.5%) of A. hydrophila isolates, while both of tetracycline resistance genes, tetA and tetC were found in 16/40 (40%) of the isolates. The strA-strB, blaTEM and blaSHV genes were not detected in any of the isolates. This present study was the first report of integron detection in A. hydrophila isolates in Malaysia. The findings obtained in this study indicated that A. hydrophila infection has become an important health issue in fish farms. Likewise, the increase of antibiotics resistant Aeromonads will lead to treatment challenge in Aeromonas infection. This study demonstrated that the presence of different combinations of the virulence genes in A. hydrophila isolates indicating their probable roles in the pathogenesis of Aeromonas infections. Results from haematological and histopathological studies provided valuable information on the extensity of pathology associated with Aeromoniasis in Oreochromis sp. Constant monitoring should be done in order to compile more information on antibiotic sensitivity of Aeromonas spp. and other known aquatic bacteria species in order to avoid the development of antibiotic superbug. The detection of resistance determinant genes in A. hydrophila is of public importance and environment significance.